Advanced Network Analysis Techniques for Social Media Study: Unveiling Patterns and Influences in Digital Communities - Jasim, Wael Abdulateef; Hussein, Ridha Ali; Basheer, Bashar Mazin; Algashamy, Hussein Ali A.; Turovsky, Oleksandr (Journal of Ecohumanism, 2024)
Background: Social media studies examine the structure and dynamics of relationships and interactions within a social network. This topic has become increasingly popular due to the widespread use of social media platforms, which generate vast amounts of data that provide insights into social structures, information flow, and influence patterns. Objective: The goal of network analysis isn social network study is to fully understand, quantify, and analyze patterns of relationships and interactions within digital social networks. Methods: In social network study, network analysis uses various approaches to extract information from the dense network of relationships in digital social networks. Using online scraping tools or platform APIs, collect user data, relationships and interactions. Studies use these technologies to learn about social structures, communication patterns, and the formation of online communities. Results: Finally, network analysis in social media study provides a comprehensive picture of the digital social landscape, delivering usable insights for various applications and contributing to a better understanding of social dynamics in the digital era.Conclusion: Network analysis in social media study reveals prominent individuals, community structures, and dynamic patterns, providing critical insights into digital interactions. The findings, which include centrality metrics, influence mapping, and textual analysis, provide significant knowledge that can be applied in marketing, public health, and other fields.